1992
DOI: 10.1016/s0006-3495(92)81926-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined influence of cholesterol and synthetic amphiphillic peptides upon bilayer thickness in model membranes

Abstract: Deuterium (2H) NMR was used to study bilayer hydrophobic thickness and mechanical properties when cholesterol and/or synthetic amphiphillic polypeptides were added to deuterated POPC lipid bilayer membranes in the liquid-crystalline (fluid) phase. Smoothed acyl chain orientational order profiles were used to calculate bilayer hydrophobic thickness. Addition of 30 mol% cholesterol to POPC at 25 degrees C increased the bilayer thickness from 2.58 to 2.99 nm. The peptides were chosen to span the bilayers with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
211
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(242 citation statements)
references
References 28 publications
(41 reference statements)
30
211
1
Order By: Relevance
“…The lipid− chain cross peaks rose similarly rapidly as in the DLPC bilayer, with an average distance of 2 Å to the lipid CH 2 . Hence, as the hydrophobic thickness of POPC membranes increased from 2.6 to 3.0 nm, 41 the macrocycle actually became closer to the lipid tails. This result provides the strongest evidence for the TM stacking model for the cyclic oligocholates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid− chain cross peaks rose similarly rapidly as in the DLPC bilayer, with an average distance of 2 Å to the lipid CH 2 . Hence, as the hydrophobic thickness of POPC membranes increased from 2.6 to 3.0 nm, 41 the macrocycle actually became closer to the lipid tails. This result provides the strongest evidence for the TM stacking model for the cyclic oligocholates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41 POPG was added to increase the colloidal stability of the liposomes in our leakage assays. 21 Inclusion of cholesterol into the POPC/POPG membrane is known to increase its hydrophobicity and hydrophobic thickness 41 but, counterintuitively, enhanced the transmembrane movement of glucose induced by 1 and 2. 21 Since hydrophobic interactions are hypothesized to drive the stacking of the oligocholate macrocycles, DLPC was chosen for its lower hydrophobicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies of model transmembrane peptides comprised of polyleucine or Ala-Leu repeats of varying lengths in model membrane systems have shown they form stable a-helices [11,[16][17][18][19][20][21][22][23][24]. These peptides commonly contain flanking tryptophans or lysines which are thought to act as anchoring residues that stabilize the helix within the bilayer and discourage peptide aggregation [18,19,22,25]. The N-and C-termini are capped (acetylated and amidated, respectively) in order to stabilize the helix dipole and to mimic continuation of the membrane-spanning segment to other regions of a membrane incorporated protein.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cholesterol has also been shown to affect the thickness of artificial bilayer systems in vitro. Extensive experimental and computational data for pure phospholipid͞cholesterol systems have demonstrated that, under certain circumstances, cholesterol increases bilayer thickness (18)(19)(20), presumably due to the ordering of the acyl chains of phospholipids. Because cholesterol is ubiquitous in eukaryotic cell membranes, it has been suggested that cholesterol is a principal modulator of bilayer thickness in these cells.…”
mentioning
confidence: 99%